The first genome‐wide association study in the Argentinian and Chilean populations identifies shared genetics with Europeans in Alzheimer's disease - Maria Carolina Dalmasso; Itziar de Rojas; Natividad Olivar; Carolina Muchnik; Bárbara Angel; Sergio Gloger; Mariana Soledad Sanchez Abalos; María Victoria Chacón; Rafael Aránguiz; Paulina Orellana; Carolina Cuesta; Pablo Galeano; et al. (My University, 2023)
AbstractINTRODUCTIONGenome‐wide association studies (GWAS) are fundamental for identifying loci associated with diseases. However, they require replication in other ethnicities.METHODSWe performed GWAS on sporadic Alzheimer's disease (AD) including 539 patients and 854 controls from Argentina and Chile. We combined our results with those from the European Alzheimer and Dementia Biobank (EADB) in a meta‐analysis and tested their genetic risk score (GRS) performance in this admixed population.RESULTSWe detected apolipoprotein E ε4 as the single genome‐wide significant signal (odds ratio  = 2.93 [2.37–3.63], P = 2.6 × 10−23). The meta‐analysis with EADB summary statistics revealed four new loci reaching GWAS significance. Functional annotations of these loci implicated endosome/lysosomal function. Finally, the AD‐GRS presented a similar performance in these populations, despite the score diminished when the Native American ancestry rose.DISCUSSIONWe report the first GWAS on AD in a population from South America. It shows shared genetics modulating AD risk between the European and these admixed populations.Highlights This is the first genome‐wide association study on Alzheimer's disease (AD) in a population sample from Argentina and Chile. Trans‐ethnic meta‐analysis reveals four new loci involving lysosomal function in AD. This is the first independent replication for TREM2L, IGH‐gene‐cluster, and ADAM17 loci. A genetic risk score (GRS) developed in Europeans performed well in this population. The higher the Native American ancestry the lower the GRS values.
Keywords: admixture; genetic risk score; genetics; genome-wide association study; hispanic; latin america; native-american ancestry; south america; apolipoprotein e; adult; alzheimer disease; american indian; argentinian; article; chile; chilean; comparative study; controlled study; endosome; european; female; gene cluster; genetic risk score; genome-wide association study; geriatric hospital; hispanic; homologous recombination; human; innate immunity; major clinical study; male; meta analysis; personalized medicine; primary health care; quality control; single nucleotide polymorphism; south america; south and central america